The African Expatriate Composer as Diplomat. Issue 2 (2nd July 2016) - van Rhyn, Chris
Abstract : Diplomacy provides us with an alternative context in which to read 'foreignness' in composition, other than the existing discourses on the forming of identities in the contexts of exile and displacement. It is a reflexive mode of critique that aims not to point out a composer's intent but, rather, to ask the composer whether the analyst's perception speaks to his intent. A brief sojourn into general diplomatic theory is followed by an overview of selected literature on music and diplomacy. Readings of contemporary art songs by the African expatriate composers Fred Onovwerosuoke (USA–Nigeria/Ghana) and Robert Fokkens (United Kingdom–South Africa) then serve to demonstrate how a reading of scores in the context of diplomacy tells us how we perceive those composers to portray an unstable concept of foreignness—being 'African'—in nuanced manners that allow acceptance with specific target audiences, and the influence that this may have on those audiences.